2010
DOI: 10.1111/j.1471-4159.2009.06533.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ca2+ signaling pathways in mouse adrenal medullary chromaffin cells

Abstract: J. Neurochem. (2010) 112, 1210–1222. Abstract In the present study, we characterized the Ca2+ responses and secretions induced by various secretagogues in mouse chromaffin cells. Activation of the acetylcholine receptor (AChR) by carbachol induced a transient intracellular Ca2+ concentration ([Ca2+]i) increase followed by two phases of [Ca2+]i decay and a burst of exocytic events. The contribution of the subtypes of AChRs to carbachol‐induced responses was examined. Based on the results obtained by stimulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 68 publications
(111 reference statements)
3
26
1
Order By: Relevance
“…It is important to note however that the effects of gastrointestinal inflammation on Ca 2ϩ signaling are not necessarily always inhibitory. For example, during TNBScolitis in guinea pigs, facilitation of synaptic transmission was observed within the submucosal and myenteric plexuses, which is unlikely to have resulted from decreased I Ca (37,41 (63). Although the present study did not assess the contribution of CICR to Ca 2ϩ signaling in ACCs during colitis, our results suggest that inhibition of I Ca is likely to be the primary cause of decreased Ca 2ϩ elevations.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…It is important to note however that the effects of gastrointestinal inflammation on Ca 2ϩ signaling are not necessarily always inhibitory. For example, during TNBScolitis in guinea pigs, facilitation of synaptic transmission was observed within the submucosal and myenteric plexuses, which is unlikely to have resulted from decreased I Ca (37,41 (63). Although the present study did not assess the contribution of CICR to Ca 2ϩ signaling in ACCs during colitis, our results suggest that inhibition of I Ca is likely to be the primary cause of decreased Ca 2ϩ elevations.…”
Section: Discussioncontrasting
confidence: 44%
“…We have previously described a decrease in I Ca of sympathetic neurons during colitis that was due to the selective inhibition of N-type Ca 2ϩ channels accompanied by a reduction in mRNA encoding the channel ␣-subunit, Ca V 2.2 (50). Therefore, we examined whether the inhibition of I Ca in ACC was associated with a selective reduction in mRNA encoding VGCC ␣-subunits in these cells: Ca V 1.2, -1.3, -2.1, -2.2, and -2.3 (3,15,29,63). Colitis caused a slight but statistically insignificant decrease in mRNA encoding Ca V 2.2, which underlies N-type channels, as well as Ca V 2.1, which underlies P/Q-type channels (Fig.…”
Section: Acute and Chronic Colitis Inhibited Depolarization-inducedmentioning
confidence: 99%
“…The role of CICR in mouse ACCs has also been addressed in recent studies. Caffeine stimulates Ca 2ϩ transients and decreases ER Ca 2ϩ concentration in mouse ACCs (26). Furthermore, these cells exhibit Ca 2ϩ scintillas, which are spontaneous ER Ca 2ϩ release events mediated by ryanodine receptors (70,71).…”
Section: Plasticity Of Ca 2؉ Release From the Er During Inflammationmentioning
confidence: 99%
“…Elevations in intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) can be achieved by Ca 2ϩ influx through voltage-gated Ca 2ϩ channels and Ca 2ϩ release from the endoplasmic reticulum (ER) (23)(24)(25). The spatiotemporal properties of the resultant Ca 2ϩ signal can also be modified by intracellular organelles (26). Ca 2ϩ signaling is a plastic process that can become altered during inflammation and infection (27)(28)(29).…”
mentioning
confidence: 99%
“…A later report showed that mouse chromaffin cells in the intact gland exhibited a smaller or nonexistent CICR [110]. However, in a recent study performed on cultured mouse chromaffin cells the expression of RyRs and a functional CICR mechanism was shown [111].…”
Section: Endoplasmic Reticulummentioning
confidence: 98%